2014
DOI: 10.1523/jneurosci.0863-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Curtailing Effect of Awakening on Visual Responses of Cortical Neurons by Cholinergic Activation of Inhibitory Circuits

Abstract: Visual responsiveness of cortical neurons changes depending on the brain state. Neural circuit mechanism underlying this change is unclear. By applying the method of in vivo two-photon functional calcium imaging to transgenic rats in which GABAergic neurons express fluorescent protein, we analyzed changes in visual response properties of cortical neurons when animals became awakened from anesthesia. In the awake state, the magnitude and reliability of visual responses of GABAergic neurons increased whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…; Kimura et al . ). Physiological and pathological role of M2 receptors located extrasynaptically on MNs is enigmatic, but functional compartmentalization shown for NMDA receptors (Papouin et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Kimura et al . ). Physiological and pathological role of M2 receptors located extrasynaptically on MNs is enigmatic, but functional compartmentalization shown for NMDA receptors (Papouin et al .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, a recent study has demonstrated that cholinergic projection from BF can modulate cortical responses to visual stimulation (Kimura et al ., ), as well as auditory stimulation (Letzkus et al ., ). Therefore, 5‐HT 1B receptor‐mediated inhibition of GABAergic inputs to BF cholinergic neurons could indirectly modulate such sensory processing in the cortex.…”
Section: Discussionmentioning
confidence: 97%
“…The application of optogenetic tools to the analysis of central cholinergic signaling using ChAT-Cre lines in either mice (Kalmbach et al, 2012 ; Huang and Zeng, 2013 ) or rats (Witten et al, 2011 ; see Figure 1 ) allows selective activation and silencing of cholinergic neurons and axonal projections, both in vitro and in vivo . Using this approach, several studies have now shown that ACh signaling occurs through direct, fast synaptic transmission—as well as over longer time scales consistent with more diffuse transmission—in the cortex (Letzkus et al, 2011 ; Arroyo et al, 2012 , 2014 ; Bennett et al, 2012 ; Kimura et al, 2014 ). Activating channelrhodopsin (ChR2) in fibers from the BF elicited a barrage of inhibitory synaptic inputs to layer (L) 2/3 pyramidal cells, which depended on nAChR activation (Arroyo et al, 2012 , 2014 ; Bennett et al, 2012 ; Kimura et al, 2014 ).…”
Section: Basal Forebrain Ach and Neocortical Functionmentioning
confidence: 99%
“…Using this approach, several studies have now shown that ACh signaling occurs through direct, fast synaptic transmission—as well as over longer time scales consistent with more diffuse transmission—in the cortex (Letzkus et al, 2011 ; Arroyo et al, 2012 , 2014 ; Bennett et al, 2012 ; Kimura et al, 2014 ). Activating channelrhodopsin (ChR2) in fibers from the BF elicited a barrage of inhibitory synaptic inputs to layer (L) 2/3 pyramidal cells, which depended on nAChR activation (Arroyo et al, 2012 , 2014 ; Bennett et al, 2012 ; Kimura et al, 2014 ). Pyramidal neurons in L2/3 apparently do not express nAChRs themselves, but L2/3 interneurons do (Poorthuis et al, 2013 ).…”
Section: Basal Forebrain Ach and Neocortical Functionmentioning
confidence: 99%
See 1 more Smart Citation